Umpan Balik Supervisi Akademik di Sekolah Menengah Kejuruan Muhammadiyah 1 Baturetno Tahun 2025 - Sutama, Sutama; Rahayu, Sri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Academic supervision should focus on providing assistance to teachers in the learning process, through constructive feedback and support for the development of teaching skills. This study aims to explore teachers' perceptions and experiences regarding academic supervision feedback at Muhammadiyah 1 Baturetno Vocational High School (SMK) in 2025. Academic supervision is a crucial instrument in improving the quality of teaching, but its effectiveness is highly dependent on the quality and utilization of the feedback provided. This study used a qualitative method with a phenomenological approach to explore in depth the meaning of academic supervision feedback from the teachers' perspective. Data were collected through in-depth interviews, observations, and document analysis. The results provide a comprehensive overview of the ongoing academic supervision feedback practices, identify strengths and weaknesses, and formulate recommendations for improving supervision practices at SMK Muhammadiyah 1 Baturetno.